Desenvolvimento e política cultural: reflexões de Celso Furtado no caminho do Ministério da Cultura - Borja, Bruno (Cadernos do Desenvolvimento, 2019)
RESUMO Amplamente reconhecido como um dos economistas mais importantes da história brasileira, Celso Furtado ainda é pouco conhecido por suas reflexões no campo da política cultural, mesmo tendo sido ministro da Cultura. No intuito de resgatar e apresentar a originalidade de seu pensamento na área, o artigo busca analisar de forma sintética suas reflexões sobre desenvolvimento e política cultural. Primeiro, será tratada sua obra anterior ao período no Ministério da Cultura, cujo núcleo se concentra na relação entre cultura e desenvolvimento. Depois, serão abordadas suas reflexões especificamente sobre política cultural, a partir de suas intervenções políticas, já no caminho do ministério. Palavras-chave: Celso Furtado; Cultura; Desenvolvimento; Política Cultural; Ministério da Cultura. ABSTRACT Widely accepted as one of the most important economists in Brazil`s history, Celso Furtado is still relatively little known for his views in the field of cultural policy, even though he once held the post of Minister of Culture. In order to try to revive and highlight the originality of his ideas on the subject, this article seeks to analyse his views on development and cultural policy in a more concise manner. The article begins by dealing with his works prior to his time in the Ministry of Culture, which were primarily focused on the relationship between culture and development. It then looks at his views more specifically aimed at cultural policy, based on the political contributions he made during his period at the Ministry. Key-words: Celso Furtado; Culture; Development; Cultural Policy; Ministry of Culture.